Heat Deflection Temperature (HDT) Properties of Polypropylene Composite Reinforced Cellulose Microfibrils of Oil Palm Empty Fruit Bunch and Frond - Wida Banar Kusumaningrum; Sasa Sofyan Munawar (Wood Research Journal, 2018)
Polypropylene composites reinforcing with natural fiber is potentially applied for automotive particularly on interior part design. Those kind of composites were contributed on renewable material, rapid rate biodegradation, and low cost of production compared to synthetic fiber. Furthermore, the mechanical properties including strenghtness, young modulus, and thermal stability have revealed good performance than glass fiber. Fiber which were fibrillated and have high aspect ratio that coresspond to diameter and lenght ratio of the fiber were noticed as enhancement factor for mechanical properties. Fiber fibrillation processing into microfibrillated cellulose (MFC) attempts for widening surface area of the fiber that improve polymer matrices compatibility. MFC from empty fruit bunches (EFB) and oil palm frond (FB) fibers were performed as pulp by mechanically and chemically treatments. Chemically treatment was conducted with bleach and unbleach procedure. Polypropylene with fiber was mixed using kneader, and injection for molding process. Manufacturing uses needs appropriate size presition, moderate lead time, and low defect. Heat deflection temperature (HDT) provide information for plastic material on indicating temperature condition effect to material deformation during normal loading. Material of origin, additive or filler size, and molding temperature were directly corelated to the HDT performance. Initial temperature of HDT exhibits different value for different kind of fillers and fiber treatments. PP/EFB composite by mechanical treatment gives high value of HDT compared to the fiber processing by chemical treatment both with bleach and unbleach process. Similar result have been performed in PP/FB composites related to initial temperature. PP/ EFB composite with 30% of fiber loading represent HDT in 149.4°C, and for PP/ FB composite with 30% fiber loading gives 150.7°C. By the addition of fiber loading could improve the HDT value of the composites.